Breaking Barriers: The Power of Diversity Tactics in Dismantling Classism from a Religious Perspective - Adeoye, Moses Adeleke; Abdulrazak, Mohammed; Fawale, Afiss Adebayo (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2025)
This study investigates the role of diversity tactics in dismantling classism, emphasizing the intersection between inclusive practices and social change. The objective is to examine how diversity initiatives, particularly those rooted in religious values of justice, compassion, and social responsibility, can challenge systemic class hierarchies. Methodologically, this research employs discourse analysis to critically assess existing literature on classism, its impact on marginalized communities, and the socioeconomic factors that sustain systemic inequities. The study explores diversity strategies implemented in educational institutions, corporate environments, and community organizations, integrating religious perspectives to highlight ethical imperatives for social equity. The findings reveal that initiatives such as affirmative action, equitable hiring practices, and community engagement effectively disrupt entrenched class structures. However, challenges such as tokenism, backlash, and resistance from dominant groups hinder their full implementation. The research underscores the necessity of adopting an intersectional approach, acknowledging how race, gender, and other social identities interact with class to create unique barriers. Religious teachings on economic justice, charity, and solidarity further reinforce the moral obligation to address class disparities. Theoretically, this study contributes to discussions on social equity by bridging diversity tactics with faith-based ethical principles, demonstrating how religious frameworks can enhance and legitimize efforts to combat classism. It calls for collaboration among policymakers, educators, faith leaders, and community advocates to foster environments where equitable access to opportunities and resources is recognized as a shared moral and social responsibility.